Comparative Study of RCCP and System Dynamics in Productivity Capacity - Purwojatmiko, B. Handoko; Cessari, Raissa Annisa; Ambarwati, Laksmi; Sumasto, Fredy (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
One of the manufacturing companies in Indonesia which is engaged in foundry has a production line for various types of automotive components and has produced 2051 types of products. One of the products produced is the Trunion Bracket. In the molding process, cores are needed that can provide cavities in the product. The current production process has not been able to meet demand because the production cycle time does not match the predetermined time. This discrepancy will affect consumer satisfaction. Therefore, it is necessary to make a schedule for the period July to December 2022, to assist companies in facilitating the scheduling of the production process using Rough Cut Capacity Planning and System dynamics. The calculation results from Rough Cut Capacity Planning indicate that the 5th workstation experienced a shortage of production time from July to September 2022, so an additional number of working hours had to be made. The addition of the number of working hours before improvement was 367 hours and after improvement was 112 hours. Meanwhile, the results of system dynamics modeling for the period July to December 2022, require an additional working hour before improvement by 308 hours and 205 hours after improvement are carried out. The companies can implement strategies based on the results of system dynamics simulations to identify, forecast, and plan production capacity requirements for the next.